2008
DOI: 10.1093/hmg/ddn274
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the expression, structure and function of progesterone receptor membrane component-1 (PGRMC1) in premature ovarian failure

Abstract: Premature ovarian failure (POF) is characterized by hypergonadotropic hypogonadism and amenorrhea before the age of 40. The condition has a heterogeneous background but genetic factors are demonstrated by the occurrence of familial cases. We identified a mother and daughter with POF both of whom carry an X;autosome translocation [t(X;11)(q24;q13)]. RNA expression studies of genes flanking the X-chromosome breakpoint revealed that both patients have reduced expression levels of the gene Progesterone Receptor Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
87
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(92 citation statements)
references
References 43 publications
0
87
1
4
Order By: Relevance
“…[t(X;11)(q24;q13)]). This X chromosome translocation likely depletes one copy of PGRMC1, thereby accounting for the reduced level of PGRMC1 in these women (Mansouri et al 2008). The second condition involves a single base mutation in which the histidine at residue 165 is changed to arginine.…”
Section: Discussionmentioning
confidence: 99%
“…[t(X;11)(q24;q13)]). This X chromosome translocation likely depletes one copy of PGRMC1, thereby accounting for the reduced level of PGRMC1 in these women (Mansouri et al 2008). The second condition involves a single base mutation in which the histidine at residue 165 is changed to arginine.…”
Section: Discussionmentioning
confidence: 99%
“…Further, a missense substitution located in the intracellular C-terminus of PGRMC1, which impair the anti-apoptotic action of progesterone in the developing ovary leading to premature ovarian follicles depletion, has been found at the heterozygous state by the genetic screening of 67 women with POI (155).…”
Section: Progesterone Receptor Membrane Componentmentioning
confidence: 99%
“…[3][4][5] Its clinical relevance is indicated by studies showing that altered PGRMC1 expression correlates with defective follicular development and infertility in women. [6][7][8] Primary evidence that PGRMC1 has a fundamental role in ovarian somatic cells comes from in vivo studies in mice, in which conditional knockout of PGRMC1 in granulosa cells impairs antral follicle development. 2,9 Accordingly, in vitro studies using different ovarian cell lines have shown that depleting PGRMC1 expression suppresses cell proliferation.…”
Section: Introductionmentioning
confidence: 99%